A Modified Porous Titanium Sheet Prepared by Plasma-Activated Sintering for Biomedical Applications. (20th December 2010) - Tamaki, Yukimichi; Lee, Won Sik; Kataoka, Yu; Miyazaki, Takashi
Abstract : This study aimed to develop a contamination-free porous titanium scaffold by a plasma-activated sintering within an originally developed TiN-coated graphite mold. The surface of porous titanium sheet with or without a coated graphite mold was characterized. The cell adhesion property of porous titanium sheet was also evaluated in this study. The peak of TiC was detected on the titanium sheet processed with the graphite mold without a TiN coating. Since the titanium fiber elements were directly in contact with the carbon graphite mold during processing, surface contamination was unavoidable event in this condition. The TiC peak was not detectable on the titanium sheet processed within the TiN-coated carbon graphite mold. This modified plasma-activated sintering with the TiN-coated graphite mold would be useful to fabricate a contamination-free titanium sheet. The number of adherent cells on the modified titanium sheet was greater than that of the bare titanium plate. Stress fiber formation and the extension of the cells were observed on the titanium sheets. This modified titanium sheet is expected to be a new tissue engineering material in orthopedic bone repair.